Hubungan Tingkat Pengetahuan Pegawai Universitas HKBP Nommensen Medan dengan Sikap dan Tindakan Pencegahan COVID-19 - Tampubolon, Inri Yana; Sipayung, Novreka Pratiwi; Saragih, Rini Amanda Carolina (Nommensen Journal of Medicine, 2023)
Background: The spread of COVID-19 has been increasingly widespread since the easing of Large-Scale Social Restrictions (PSBB). This increases community activities outside the home, especially office employees who have started working, so that the office becomes the largest source of transmission clusters. Breaking the chain of spreadof COVID-19 requires a good balance between knowledge, attitudes, and preventive measures for COVID-19. Individual knowledge about COVID-19 based on appropriate information is the most important domain in shaping individual behavior. It is hoped that this good knowledge can influence every individual in showing a positive attitude and good action in preventing and controlling COVID- 19.Objective: This study aimed to determine the relationship between the level of knowledge of the campus staff of the Universitas HKBP Nommensen Medan on the attitudes and actions to prevent Coronavirus Disease 2019 (COVID-19).Methods: This study was an analytic study using a cross sectional design. The number of samples is 86 people who were selected using purposive sampling method. The data obtained are primary data from questionnaires that have been filled out by the research sample.Results: The results of this study showed 86 respondents, good knowledge level (97.7%), positive attitude (90.7%) and good action (84.9%). In the bivariate analysis, it was stated that there was a statistically significant relationship between knowledge and preventive measures for COVID-19 (p=0.021).Conclusion: Good knowledge was expected to have a good impact on prevention and transmission of COVID-19. Key Words : COVID-19, knowledge, attitude, precautions.